2015
DOI: 10.1149/2.0151601jes
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Supporting Electrolytes on Zinc Half-Cell Performance in Zinc/Bromine Flow Batteries

Abstract: Five supporting electrolytes were studied for their viability as alternatives in the zinc half-cell of a zinc/bromine (Zn/Br) flow battery. The secondary electrolytes studied included sodium salts of the following anions: Br -, SO 4 2-, H 2 PO 4 -and NO 3 -, which were compared against the conventionally employed Cl -. Cyclic voltammetry and Tafel analysis showed improved electrochemical performance from electrolytes containing NaBr, Na 2 SO 4 and NaH 2 PO 4 . Consequently, these chemicals are proposed as pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 38 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…The bipolar, symmetric Zn−Fc AORFB was examined using 0.5 M Zn[Fc(SPr) 2 ] (13.4 Ah L −1 and 7.6 Wh L −1 ) in 3.0 M NH 4 Br aqueous solution as both an anolyte and a catholyte, as well as a low‐cost Daramic membrane ($1/m 2 ). It should be noted that the use of the NH 4 Br supporting electrolyte instead of NH 4 Cl is because the Br − anion is more beneficial than the Cl − anion for the Zn deposition and stripping, including faster deposition/stripping kinetics and smoother Zn morphology [27] . Because of the divalent nature of the Zn 2+ ion, the volume ratio of the catholyte and anolyte was 2 : 1, giving an energy density of 10.1 Wh L −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bipolar, symmetric Zn−Fc AORFB was examined using 0.5 M Zn[Fc(SPr) 2 ] (13.4 Ah L −1 and 7.6 Wh L −1 ) in 3.0 M NH 4 Br aqueous solution as both an anolyte and a catholyte, as well as a low‐cost Daramic membrane ($1/m 2 ). It should be noted that the use of the NH 4 Br supporting electrolyte instead of NH 4 Cl is because the Br − anion is more beneficial than the Cl − anion for the Zn deposition and stripping, including faster deposition/stripping kinetics and smoother Zn morphology [27] . Because of the divalent nature of the Zn 2+ ion, the volume ratio of the catholyte and anolyte was 2 : 1, giving an energy density of 10.1 Wh L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the use of the NH 4 Br supporting electrolyte instead of NH 4 Cl is because the Br À anion is more beneficial than the Cl À anion for the Zn deposition and stripping, including faster deposition/stripping kinetics and smoother Zn morphology. [27] Because of the divalent nature of the Zn 2 + ion, the volume ratio of the catholyte and anolyte was 2 : 1, giving an energy density of 10.1 Wh L À 1 . The 0.5 M ZnÀ Fc AORFB was charged/discharged within a voltage window of 0.2 and 1.35 V. As shown in Figures 4B and C, the 0.5 M Zn[Fc(SPr) 2 ] symmetric AORFB was smoothly cycled under high current densities of up to 200 mA cm À 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, dual halogen electrolytes were reported to increase the working voltage window and provide higher energy density due to the combination of different redox reactions. [131][132][133] For instance, Liu et al reported a Br and Cl-containing molten hydrate electrolyte. [134] The dual ion electrolyte enabled the possibility of ion intercalation in carbon materials used at the cathode side (Figure 18a).…”
Section: Electrolytesmentioning
confidence: 99%
“…Rajarathnam et al [86] have studied the effect of 0.5 mol dm -3 Br-, SO4 -, H2PO4and NO3anions on the electrode kinetics of the Br -/Br2 reaction. As shown in Figure 6, these supporting electrolytes resulted in different deposit morphologies.…”
Section: Development Continued Over the Next Decade Under The Directimentioning
confidence: 99%